Mathematical modeling of two strains tuberculosis and COVID-19 vaccination model: a co-infection study with cost-e􀀀ectiveness analysis - Appiah, Raymond Fosu; Jin, Zhen; Yang, Junyuan; Asamoah, Joshua Kiddy K.; Wen, Yuqi (Frontier, 2024)
This article is published by Frontiers 2024 and is also available at 10.3389/fams.2024.1373565